Contralateral hemisphere activation by unilateral hand contraction: reexamining global and local attention - Stanković, Miloš; Nešić, Milkica (Perceptual and motor skills, 2018)
While previous studies have shown that left- (vs. right-) hand contractions can improve the performance of global (vs. local) attention, these results were inconsistent in certain behavioral studies in which the left cerebral hemisphere was found to be specialized for local attention, while the right hemisphere was not specialized for global attention. Thus, we reexamined whether different global (vs. local) attention performances follow left- (vs. right-) hand contractions due to right (vs. left) hemisphere activation. We recruited 100 right-handed healthy female, university student (aged 19-26 years) participants. We used the Navon task to present 80 letter-stimuli (40 in the global task; 40 in the local task) to either the participants’ left or right visual fields. Half of the participants (randomly selected) were instructed to squeeze a dynamometer with the left hand, while the other half squeezed with the right hand, prior to completing the Navon task. In line with previous research, we observed a perceptual advantage of global (large letters) over local (small letters) stimuli. Participants who contracted the right hand showed an enhanced local attention performance (from left hemisphere activation), whereas those who contracted the left hand did not improve global attention performance (from right hemisphere activation). Thus, we supported prior behavioral research suggesting that hemispheric asymmetry for attention processing is evident for left but not right cortical hemisphere processing.